Sustainable agro-pisciculture systems in Sub-Saharan Africa - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2001)
The overall objective of the study visit was to focus on the development of sustainable strategies for the dissemination of knowledge about integrated agriculture-aquaculture farming systems as a realistic option for smallholder farmers by analysing the a